A Review of Strategic for the Development of the Paraman Ampalu – West Pasaman Regency Based on Physical and Economic Conditions - Dedi Hermon (Science and Environmental Journal for Postgraduate, 2023)
This study aims to examine the physical aspects (geology and geomorphology, and economics, as well as strategic policy directions for the development of the Paraman Ampalu area in Gunung Tuleh Sub-district (SWOT). This literature topic will explain geological, geomorphological, and human conditions in economic development. The information presented is based on reliable sources, so it is expected to provide an accurate and comprehensive picture of the geography of the area.